Perioperative outcomes of off‐clamp vs complete hilar control laparoscopic partial nephrectomy. (6th November 2012) - George, Arvin K.; Herati, Amin S.; Srinivasan, Arun K.; Rais‐Bahrami, Soroush; Waingankar, Nikhil; Sadek, Mostafa A.; Schwartz, Michael J.; Okhunov, Zhamshid; Richstone, Lee; Okeke, Zeph; Kavoussi, Louis R.
Abstract : What's known on the subject? and What does the study add? Off‐clamp laparoscopic partial nephrectomy (LPN) is thought to preserve renal function by limiting warm ischaemia time (WIT) and consequently reperfusion injury. To date, studies using the off‐clamp technique represent a heterogeneous group, with limited follow‐up showing feasibility and safety in a restricted number of cases. We report the largest experience of off‐clamp vs on‐clamp LPN with perioperative outcomes and intermediate follow‐up of renal functional outcomes with stratification by WIT. OBJECTIVE: To evaluate perioperative and 6‐month renal functional outcomes of patients undergoing off‐clamp vs complete hilar control laparoscopic partial nephrectomy (LPN). PATIENTS AND METHODS: A retrospective review of 489 patients undergoing LPN was completed. Preoperative imaging assessed tumour characteristics. Patient demographics, perioperative parameters, and postoperative outcomes were documented. Multivariable regression analysis was used to assess factors contributing to changes in postoperative renal function between off‐clamp and clamped LPN. RESULTS: In all, 289 LPNs were performed on‐clamp and 150 were performed off‐clamp. Tumours in the on‐clamp group were larger than those in the off‐clamp group (mean [range] 3.3 [0.5–13.5] vs 2.7 [0.4–9] cm, P = 0.003). Univariable analysis comparing off‐clamp to on‐clamp cohorts showed that estimated glomerular filtration rate (eGFR) was better preserved in the off‐clamp cohort at 6 months (−5.8% vs –11.4%, P = 0.046). Multivariable analysis of the groups showed that estimate blood loss ( P = 0.015) and warm ischaemia time (WIT, P < 0.001) were the only significant predictors of decreased eGFR in the postoperative period. Difference in eGFR at 6 months was not significant when WIT was limited to 30 min. The complication rate was greater in the clamped cohort (10% vs 20%, P = 0.012). There was no difference in transfusion rate or positive margin status. CONCLUSIONS: LPN without hilar clamping is feasible, safe and associated with less renal injury as assessed by postoperative GFR in select patients. With experience, it can be applied to complex renal lesions.